PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KERJA PEGAWAI ORGANIK GMIH DI TOBELO - Talimbo, Delia (Universitas Sam Ratulangi, 2013)
Human resources have an important role in an organization, since all aspects related to human resources will also affect the growing emerging an organization in improving employee job performance. Improvement of the performance of an officer is the important thing in an organization or a company even though it was realized that in practice it is not easy. This research aims to know the influence of the working culture, work environment, job satisfaction on performance orgnic employee Kantor Sinode GMIH in Tobelo. Using the method of path analysis. Inferred variable working culture (X 1), and the work environment (X 2) simultaneously influence significantly to the performance of an employee's organic Kantor Sinode GMIH in Tobelo, F values obtained for sub structure with a value of 1 for 17,981 sing 0,000. Testing sub truktur 2 with Variable work culture (X 1), the working environment (X 2), job satisfaction (Y1) simultaneously influence work performance significantly to orgnik employees in the Office of the Synod of GMIH, obtained a value of 36, F 508-value sig 0.000. While individually testing variables work culture (X1) effect significantly to value employee performance table coeficients 0.273 sig value 0.008, variable job satisfaction (Y1) effect significantly to the performance of the work of the organic Kantor Sinode GMIH in tobelo with value 0,571 and value sig 0.000. Â Keywords: work culture, work environment, job satisfaction and performance of employees.